Global survey of consumer organizations advocating for safer nicotine products. Issue 1 (19th January 2023) - Jerzyński, Tomasz; Harding, Jessica; Stimson, Gerry V.
Abstract: Introduction: The study investigated the role and activities of organizations that advocate for the adoption of and access to safer nicotine products (SNPs), such as nicotine vaping products (e‐cigarettes), Swedish‐style snus, nontobacco nicotine pouches, and heated tobacco products, as safer alternatives to combustible cigarettes and other high‐risk tobacco products, following a harm reduction approach. The aim was to map the number and locations of nicotine consumer organizations globally and describe their history, legal status, membership, structure, objectives, working methods and activities, and funding. Methods: We identified active organizations through the use of existing networks and referrals. All identified organizations were contacted and asked to fill in an online self‐completion survey through the representatives of the organizations. The data collected were cleaned and anonymized. Categorization and analysis of variable distributions were carried out. Responses to open–ended questions were analyzed qualitatively. Results: A total of 52 active organizations were identified: 13 in Latin America, 8 in Africa, 24 in Europe, 5 in the Asia‐Pacific region, and 2 in North America. Most were established from 2016 onward, and 39 were legally incorporated. Their reported objectives were to raise awareness about SNP, promote rights to access SNP, and advocate for a legal and regulatory environment in which SNPs are available. They are small organizations: Most are operated with volunteers, with only 7 having any contracted or paid staff, and only 13 persons globally with a paid position. A total of 31 organizations had not received any funding support. The total global funding for all organizations was US$ 309, 810. None reported receiving funding from tobacco or pharmaceutical companies. All pointed to important achievements in the public debate about SNP and tobacco harm reduction. Conclusion: The organizations are run by enthusiastic individuals, most of whom have successfully quit smoking with the help of SNP. Organizations depend on the input of a small number of core workers, all organizations are under‐resourced and potentially fragile, and yet, they report significant activity and success. The challenge for these groups is to gain recognition at national and international level as legitimate stakeholders in the development of tobacco control policy with respect to safer alternatives to smoking.